2003
DOI: 10.1037/1091-7527.21.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Differentiation of Self and the Stress and Distress Associated With Predictive Cancer Genetic Counseling and Testing: Preliminary Evidence.

Abstract: Cancer Genetics Program for their help in this endeavor. We especially thank Kevin Sweet, M.A. for his help with data collection. associated with the stress associated with the counseling and/or testing situation, and psychological distress for both probands and study partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
(53 reference statements)
1
11
0
Order By: Relevance
“…This finding is in line with Bowen’s (1978) theory that poorly differentiated individuals tend to exhibit more psychopathology. It is also in line with previous studies that found a significant connection between poor differentiation and various psychiatric problems (e.g., Bartle‐Haring & Gregory, 2003; Tuason & Friedlander, 2000). More specifically, the finding that cut‐off is related to emotional distress may stem from the fact that this state of over‐differentiation corresponds to and reminds ex‐POWs of the original experience of captivity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in line with Bowen’s (1978) theory that poorly differentiated individuals tend to exhibit more psychopathology. It is also in line with previous studies that found a significant connection between poor differentiation and various psychiatric problems (e.g., Bartle‐Haring & Gregory, 2003; Tuason & Friedlander, 2000). More specifically, the finding that cut‐off is related to emotional distress may stem from the fact that this state of over‐differentiation corresponds to and reminds ex‐POWs of the original experience of captivity.…”
Section: Discussionsupporting
confidence: 92%
“…Empirical findings support these claims regarding the ability of highly differentiated individuals to manage stress. Highly differentiated individuals were found to suffer from lower levels of avoidant and intrusive thoughts (Bartle‐Haring & Gregory, 2003), general psychiatric distress (Tuason & Friedlander, 2000), behavioral dysfunctions (Haber, 1993), trait anxiety (Griffin & Apostal, 1993), and depression (Elieson & Rubin, 2001).…”
Section: Differentiation Stress and Distressmentioning
confidence: 99%
“…Bartle-Haring and Probst (2004) found that for reactivity to mother, passive reactivity predicted psychological symptoms, but not stressful life events, while for reactivity to father, passive and active reactivity predicted psychological symptoms in a clinical sample. Bartle-Haring and Gregory (2003) also found that higher levels of differentiation in the participant and the study partner were associated with less stress and distress experienced with genetic counseling and/or testing for cancer. They concluded that differentiation of self might provide a buffer against the stress that may accompany genetic counseling and testing and thus result in less psychological distress.…”
Section: Differentiation Of Selfmentioning
confidence: 85%
“…Studies were considered eligible for inclusion in the literature review if they were published in a peer-reviewed journal and were in the English language. A systematic literature search yielded 10 published studies on at-risk women and their male partners [7,12,24,[41][42][43][44][45][46][47]. All studies either primarily investigated partners of high-risk women or included partners when investigating women themselves; however, one of these studies [45] did not investigate male partner distress as an outcome variable.…”
Section: Literature Search Strategymentioning
confidence: 99%